Reseña de Penas Ibáñez, M.ª Azucena (2018): El cibertexto y el ciberlenguaje - De Arcos Pastor, Angustias (Pragmalingüística, 2020)
Se trata de una reseña de Penas Ibáñez, M.ª Azucena (2018): El cibertexto y el ciberlenguaje.